Analisis Kerjasama Antara Anggota TNI dan Pemerintah Daerah Papua dalam Menangani Konflik di Papua - Richard Arnold Yeheskiel Sangari (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
The province of Papua has long been affected by conflicts involving political issues, autonomy, ethnic diversity, natural resources, and human rights. This conflict began during the colonial period and continued after Papua became part of Indonesia in 1945, particularly following the 1969 Pepera, which many Papua residents deemed unfair. Violence in Papua persists with numerous casualties, reflecting a severe security situation. Conflict management efforts involve synergy between the TNI and local government, with the TNI focusing not only on security but also on social and economic development. Collaboration between territorial apparatus and local government is expected to create stability but often faces challenges such as differing task perceptions and support for separatist groups. This study employs a qualitative research method with a case study approach, using interviews and literature review to gather data. The findings indicate that handling the conflict in Papua requires strategic measures, including increasing the presence of Satuan Komando Wilayah (Satkowil) at each administrative level, such as Kodim in districts and Koramil in sub-districts. Kodim and Koramil play a crucial role in maintaining security and supporting local development and community welfare. It is also important to map various types of conflicts—armed, communal, and social—and adopt appropriate approaches. Satkowil/Apter serves as a communication bridge between local government and the community, assisting in policy implementation and addressing conflicts proactively. Effective collaboration between territorial apparatus and local government is expected to enhance stability and progress in Papua.